THE RELEVANCE OF THE ETHICS OF JOURNALISTIC CODE FOR COVID-19 NEWS REPORTING IN ONLINE MEDIA - Junaidi Junaidi; Ismail Arafah (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
Since Coronavirus Disease 2019 (COVID-19) was announced in Indonesia in March 2020, information about COVID-19 has become the headlines news in various mass media, newspaper, electronic and online. Every day, the information about the COVID-19 cases are easily obtained and shared by the public, especially information that comes from online media. Meanwhile, broadcasting and disseminating news by online media makes it easy for the public to get information update about COVID-19 quickly. But on the other side, the way of online media reporting that depend on how quick the news to deliver, often ignoring the element of accuracy in the news. This is violate the provisions that have been determined in the ethics of journalistic code. From the observations that has been done by several online media, COVID-19 reporting leads to a violation of the ethics of journalistic code. Its because the data that used as news material only comes from the COVID-19 Task Force, from national and regional levels. The data are immediately used as news without going through any further verification processes or checks and rechecks. As the result, the news that is done will cause refraction. Furthermore, there are some news that provides by online media which is openly mention the identity of the patient or victim of COVID-19. The study wants to answer how the Relevance of the Ethics of Journalistic Code to COVID-19 in Online Media through a qualitative descriptive method.Keywords: The Ethics of Journalistic Code, COVID-19, Online Media